FEMALE ASPECTS IN THE CONTEMPORARY AFRO-BRAZILIAN ORAL POETICS: WOMEN REPRESENT BY MAE BEATA DE YEMONJA - Alves-Garbim, Juliana Franco [UNESP] (Centro Ensino Superior Juiz De Fora, 2020)
The present article addresses some aspects of female figures, may it be in the construction of characters, or in the process of narrating Afro-Brazilian stories. The text approaches excerpts of short stories written by Mae Beata de Yemonja, focusing on the role of the feminine in maintaining the Afro-Brazilian oral tradition. From a methodological standpoint, the study presents a theoretical-descriptive analysis concerning the representation of Afrofemale poetic voices in contemporary oral and popular culture. The bibliographic references applied features literary theory, such as Gilberto Freyre (2003), Walter Benjamin (1994), Zila Bernd (1987), Stuart Hall (2003), Eduardo de Asiss Duarte (2011) among other researchers in the field of oral literature and female writing on memory and cultural identity. The research relevance is understood when it comes to searching for the comprehension of women's role in the propagation of customs and maintenance of the Afromatricial culture. The initial presumptions are that the female voices present in the narrative framework of the author highlighted come from an Afrocentric matrix, specifically from Yoruba Africa, cultural soil of the matrilineal oral tradition that migrated to Brazil. Moved by the Black diaspora, African women brought with them the strength of their voice and the sacred feminine. Given this, this article tried to make evident through the storyteller Mae Beata de Yemonja, the power of ancestral blackness, aside from understanding the female archetypes that comprise her authorial voice.
Keywords: Afro-Brazilian oral poetic; matrilineal culture; ancestry